The Association Between Saturated Fat Intake and Central Obesity and Elevated Hypertension Among Communities and Monasteries of The Archdiocese of Ende - Ire, Yohana Helena Fiorola; Wungouw, Herman P. L; Asa, Helena Meldy; Woda, Rahel Rara (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Central obesity and hypertension are major public health problems contributing substantially to the burden of non-communicable diseases. Excess saturated fat intake plays an important role in visceral fat accumulation and blood pressure elevation, particularly in populations with distinctive lifestyles and dietary patterns such as religious communities and monasteries. This study aimed to determine the association between saturated fat intake and central obesity as well as elevated hypertension among members of communities and monasteries of the Archdiocese of Ende. An observational analytic study with a cross-sectional design was conducted. A total of 50 respondents were selected using simple random sampling. Saturated fat intake was assessed using a Semi-Quantitative Food Frequency Questionnaire, central obesity was determined by waist circumference measurement, and elevated hypertension was identified through blood pressure assessment. Data were analyzed using the Chi-Square test with a significance level of α = 0.05. Most respondents had normal saturated fat intake (50.0%), followed by high intake (40.0%). Central obesity was observed in 72.0% of respondents, and 40.0% were classified as having elevated hypertension. Bivariate analysis demonstrated a significant association between saturated fat intake and central obesity (p = 0.001) as well as elevated hypertension (p = 0.009). There is a significant association between saturated fat intake and both central obesity and elevated hypertension among members of communities and monasteries of the Archdiocese of Ende.